The Impact of Being a Subsidiary on the Process of Formulating and Implementation of the Strategy in Polish Small Enterprises - Krzysztof ĆWIK (Communications of International Proceedings, 2021)
One of the criteria for differentiating small-sized enterprises is whether or not they are subsidiaries of a corporate group (a.k.a. a business group or a group of companies). It seems to be quite important for research in management science. The paper presents the results of the study on the implementation of a strategy and the strategy formulation process in small-sized enterprises. The results showed quite significant differences depending on whether or not the enterprises were subsidiaries of a corporate group. These differences may become a starting point for a discussion on the importance of this feature in management science.
Keywords: Small-Sized Enterprise; Strategy; Subsidiary; Corporate Group.